Estimating the Coronal Supra-Arcade Downflow Radio Emission: From Centimeter Through Submillimeter Wavelengths - Zurbriggen, Ernesto; Giménez De Castro, C. Guillermo; Costa, Andrea; Cécere, Mariana; Selhorst, Caius L. (Frontiers in Astronomy and Space Sciences, 2022)
Supra-arcade downflows (SADs) are infrequent, wiggly, and low-emission structures observed to descend through the solar corona, mostly in EUV and soft X-ray frequencies. Based on their physical characteristics, SADs have been interpreted as low-density bubbles and are related to magnetic reconnection processes during long-term erupting flares. In this work, we use numerical MHD simulations to compute flux density maps, which are convolved with telescope beams to synthesize images with the aim to assess the expected SAD emission in radio wavelengths. We assume that the emission is thermal bremsstrahlung from a fully ionized plasma and without any appreciable gyroresonance contribution since magnetic fields are of the order of 10 G. We find that SAD emission should be optically thin in the frequency range of [10–1,000] GHz, and the spatially integrated flux should be larger than 1 Jy. We conclude, therefore, that SADs consistently are less bright than the surrounding fan and that observing SADs in radio frequencies between [0.5–1,000] GHz is feasible with present instrumentation. The observing strategies are proposed, including the instruments that can be used. Moreover, since the emission is, for the most part, optically thin, the flux density is proportional to temperature, density, and line-of-sight depth and when combined with EUV and soft X-ray images may allow a better density and temperature determination of SADs.